Amino acid-derived alternating polyampholyte luminogens. Issue 24 (20th May 2019) - Saha, Biswajit; Choudhury, Neha; Bhadran, Abhi; Bauri, Kamal; De, Priyadarsi
Abstract : A unique polyampholyte luminogen comprised of alternatively placed oppositely charged moieties onto the poly(styrene- alt -maleimide) skeleton was synthesized, and used for the specific detection of carbon disulfide (CS2 ) in both solution and vapor phases. Abstract : Herein, a leucine-based perfectly alternating polyampholyte was synthesized by placing positively charged primary ammonium groups and negatively charged carboxylate groups alternatively onto the side chain of the poly(styrene- alt -maleimide) skeleton. The well-defined non-ionic macromolecular precursor was first prepared by sequence-controlled reversible addition–fragmentation chain transfer (RAFT) copolymerization of an N -maleoyl-l -leucine tert -butyl ester (M1 ) with a tert -butyl carbamate (Boc)-protected leucine appended styrenic monomer (M2 ), which could serve as an anionic and a cationic unit of the co-zwitterion monomers respectively, as a result of exclusion of the protecting groups. The aqueous solution behavior of the polyampholyte was studied by a combination of techniques, including pH, turbidity and zeta potential measurements, revealing net zero charge (isoelectric point (IEP)) with concomitant phase separation at pH = 7.0. The protected version of the as-synthesized copolymer displayed intense blue luminescence only in organic solvents, albeit it does not contain any conjugated fluorophore moiety. Interestingly, the alternating polyampholyte exhibited fluorescence activity in water and was used for the specific detection of carbon disulfide (CS2 ) among various volatile organic compounds (VOCs) in a 100% aqueous environment. Moreover, the polyampholyte could accomplish a colorimetric "naked-eye" sensing of CS2 vapour with high selectivity and sensitivity under ambient conditions.